Das Erbe der "Helden" Grabkult der Konso und kulturverwandten Ethnien in Süd-Äthiopien - Poissonnier, Nicole (Universitätsverlag Göttingen, 2009)
The publication focusses on the "waakaa", antropomorphic wooden sculptures of the Konso in Ethiopia. The study highlights the social functions and meanings of the sculptures. Besides a detailed description it also includes information on their production, the corresponding rituals and the way the statues are erected.